Normal Hematopoietic Progenitor Subsets Have Distinct Reactive Oxygen Species, BCL2 and Cell-Cycle Profiles That Are Decoupled from Maturation in Acute Myeloid Leukemia. - Naeem Khan; Robert K Hills; Steve Knapper; Lora Steadman; Ushna Qureshi; Jerrald L Rector; Charlotte Bradbury; Nigel H Russell; Paresh Vyas; Alan K Burnett; David Grimwade; Paul S Hole; et al. (PLoS ONE)
In acute myeloid leukemia (AML) quiescence and low oxidative state, linked to BCL2 mitochondrial regulation, endow leukemic stem cells (LSC) with treatment-resistance. LSC in CD34+ and more mature CD34- AML have heterogeneous immunophenotypes overlapping with normal stem/progenitor cells (SPC) but may be differentiated by functional markers. We therefore investigated the oxidative/reactive oxygen species (ROS) profile, its relationship with cell-cycle/BCL2 for normal SPC, and whether altered in AML and myelodysplasia (MDS). In control BM (n = 24), ROS levels were highest in granulocyte-macrophage progenitors (GMP) and CD34- myeloid precursors but megakaryocyte-erythroid progenitors had equivalent levels to CD34+CD38low immature-SPC although they were ki67high. BCL2 upregulation was specific to GMPs. This profile was also observed for CD34+SPC in MDS-without-excess-blasts (MDS-noEB, n = 12). Erythroid CD34- precursors were, however, abnormally ROS-high in MDS-noEB, potentially linking oxidative stress to cell loss. In pre-treatment AML (n = 93) and MDS-with-excess-blasts (MDS-RAEB) (n = 14), immunophenotypic mature-SPC had similar ROS levels to co-existing immature-SPC. However ROS levels varied between AMLs; Flt3ITD+/NPM1wild-type CD34+SPC had higher ROS than NPM1mutated CD34+ or CD34- SPC. An aberrant ki67lowBCL2high immunophenotype was observed in CD34+AML (most prominent in Flt3ITD AMLs) but also in CD34- AMLs and MDS-RAEB, suggesting a shared redox/pro-survival adaptation. Some patients had BCL2 overexpression in CD34+ ROS-high as well as ROS-low fractions which may be indicative of poor early response to standard chemotherapy. Thus normal SPC subsets have distinct ROS, cell-cycle, BCL2 profiles that in AML /MDS-RAEB are decoupled from maturation. The combined profile of these functional properties in AML subpopulations may be relevant to differential treatment resistance.